ANALISIS GAYA BAHASA PADA KUMPULAN CERPEN DEWI LESTARI DALAM BUKU RECTOVERSO - Noviani Pahlina; Hani Nurfiani Hanafi; Dida Firmansyah; Rosi Rosi (IKIP Siliwangi, 2019)
This research has a purpose to find out what style of language that Dewi Lestari used in her short stories in a book called Rectoverso. The method used is descriptive qualitative research method with stalistika and structural approach. From the data that has been analyzed this study obtained a conclusion that the style of language used is the first language style of parallelism, anticlimactic, climax, repetition and antithesis. Of the total there are 45 language styles, consisting of 4 parallelisms, 5 anticlimaxes, climax 10, repetition 17 and antithesis 9. Both direct language styles have no meaning with the total of 75 language styles. 47 is rhetorical, divided into 8 types of hyperbola 11, correction 1, eroteris 5, ellipsis 1, alitrasi 6, asindenton 4, asonasi 11, and perifrasis 2. Next 28 is a metaphor divided into 3 namely simile 20, metonimia 4, and personification 4.